2023
DOI: 10.15586/aei.v51i2.760
|View full text |Cite
|
Sign up to set email alerts
|

CHAC1 exacerbates LPS-induced ferroptosis and apoptosis in HK-2 cells by promoting oxidative stress

Abstract: Background: Sepsis-induced acute kidney injury (AKI) is a singularly grievous and life-threatening syndrome. Its pathogenesis is closely related to inflammatory response, apoptosis, oxidative stress, and ferroptosis. Cation transport regulator-like protein 1 (CHAC1), as a proapoptic factor, may be involved in apoptosis, oxidative stress, and ferroptosis. This study aimed to explore the role of CHAC1 in the lipopolysaccharide (LPS)-induced the human renal proximal tubular epithelial (HK-2) cells. Methods: HK-2 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 36 publications
0
4
0
Order By: Relevance
“… 35 identified a specific maladaptive/profibrotic PT cluster that expressed proinflammatory and profibrotic cytokines and was associated with the activation of inflammatory cell death pathways (pyroptosis and ferroptosis). In our STC transcriptomic data, we could identify genes that are associated with ferroptosis (e.g., Chac1, Acsl4, Hmox1 ), 40 , 41 , 42 particularly in the STC-S3 fraction ( Data S3 ). Balzer et al.…”
Section: Discussionmentioning
confidence: 99%
“… 35 identified a specific maladaptive/profibrotic PT cluster that expressed proinflammatory and profibrotic cytokines and was associated with the activation of inflammatory cell death pathways (pyroptosis and ferroptosis). In our STC transcriptomic data, we could identify genes that are associated with ferroptosis (e.g., Chac1, Acsl4, Hmox1 ), 40 , 41 , 42 particularly in the STC-S3 fraction ( Data S3 ). Balzer et al.…”
Section: Discussionmentioning
confidence: 99%
“…EHT 1864 and phospholipase inhibitor (salubrinal) were effective in targeted treatment of cell ferroptosis and patients with SA-AKI. Zhou et al 81 also verified the existence of ferroptosis in the pathogenesis of SA-AKI after establishing the mouse model of SA-AKI. It was found that cationic transport regulator-like protein 1 could promote the ferroptosis of HK-2 cells by enhancing the oxidative stress induced by lipopolysaccharide.…”
Section: Ferroptosis and Sepsis-induced Akimentioning
confidence: 92%
“…In addition, treatment with ferroptosis inhibitors has been shown to effectively alleviate IRI-AKI in mice model [ 327 , 330 ]. Ferroptosis is also increased in sepsis-induced AKI mouse models [ 331 ]. Recent studies have demonstrated that treatment with melatonin prevents ferroptosis and ameliorates sepsis-associated AKI by upregulating Nrf2/HO-1 cytoprotective pathway [ 332 ].…”
Section: The Crosstalk Of Abnormal Iron Metabolism and Oxidative Stre...mentioning
confidence: 99%